(3GdQSGdI aj GdYbhOs - (3Gdbej, GdejQRG Gdbej, Gdbej, CHh GdbGSe Hf eMeO MSjf Gdbej, J (B1231(3g` (B1816(3es
(3ChdgG (B:s
(3ChdgG(B: (3hGdXGgQ Cf LhGRg Cj GdTQW aj GdLedI GLeGYjf YfO YedGFfG aj GdYbhO hCeG GdEjbGYGJ ajLhR aj HYVgG cGdYJbs
(3BNQgG (B:s
(3BNQgG(B: (3dG jbJVjg GdebGe dJMbb CUd eYfi GdJYdjb HWhO GSJaGA heG jJYdb Hg aEf ehVhY GdQSGdI gh GdTQW ef GdQSGdI GdeUfhYI aj GdTQW aj NeS GdYbOs
(3JHUQI GdYfhGf (B:s
(3dYd gPg GdQSGdI LRA ef QSGdI(B: (3GdTQW aj Vef GdYbO ddeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 183s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3Gdabg GdYGes